The Role of Parents in Preventing Deviant Behavior (Case Study of Adolescents Aged 13-18 Years in Setu Wetan Village, Weru District, Cirebon Regency) - Agung, Agung; Mutia, Tri; Syathori, A. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research is motivated by the fact that there are still gaps in adolescent moral development. Some parents are still not optimal in educating adolescents, so some teenagers do not have morals well, or often there is deviant behavior of adolescents. This study aims to obtain data on the role of parents in adolescent moral development, deviant behavior of adolescents aged 13-18 years, and the relationship between the role of parents to moral development in preventing deviant behavior of adolescents aged 13-18 years in Setu Wetan Village, Weru District, Cirebon Regency. This research method uses quantitative research. Data collection techniques use observation, questionnaires, and documentation. Data analysis techniques use quantitative descriptive analysis. The results of this study, the Role of Parents in Adolescent Moral Development, is included in the Good Category with a score of 89.6%. Deviant Behavior of Adolescents Aged 13-18 years is included in the Good Category with a score of 84%. There is a positive and significant relationship between the Role of Parents in Adolescent Moral Development in preventing Deviant Behavior of Adolescents Aged 13-18 in Setu Wetan Village Weru Subdistrict, Cirebon Regency, the relationship is 1.69%, and other factors influence the remaining 98.31%.